2002
DOI: 10.1097/00006223-200211000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Web-based Teaching in Undergraduate Nursing Programs

Abstract: This study examined faculty perspectives of teaching undergraduate nursing courses entirely online via the World Wide Web. More than 80% of the 171 faculty completing the online survey indicated spending more time planning and implementing a Web course than a traditional course. Forty-seven percent preferred online teaching to traditional instruction, and described the experience as a success beyond expectation. This positive reaction supports the ongoing viability of Web-based instruction in nursing education. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 6 publications
0
15
1
Order By: Relevance
“…In fact, Bolliger and Wasilik (2009) found that some of the most significant institutional issues affecting faculty satisfaction were a higher workload and increased time commitment for online instructors. Many other studies have acknowledged issues of substantial time commitments and workload for online faculty (Bacow et al, 2012;Christianson et al, 2002;Conceição, 2006;DeGagne & Walters, 2010;Green et al, 2009;Haber & Mills, 2008;Mason et al, 2010). Most research has shown that time commitment and workload were barriers or demotivators to faculty, though some studies claimed that the extra time commitment did not affect faculty satisfaction or preference for teaching online (Christianson et al, 2002;Orr et al, 2009;Shea et al, 2005).…”
Section: Results Demonstrabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, Bolliger and Wasilik (2009) found that some of the most significant institutional issues affecting faculty satisfaction were a higher workload and increased time commitment for online instructors. Many other studies have acknowledged issues of substantial time commitments and workload for online faculty (Bacow et al, 2012;Christianson et al, 2002;Conceição, 2006;DeGagne & Walters, 2010;Green et al, 2009;Haber & Mills, 2008;Mason et al, 2010). Most research has shown that time commitment and workload were barriers or demotivators to faculty, though some studies claimed that the extra time commitment did not affect faculty satisfaction or preference for teaching online (Christianson et al, 2002;Orr et al, 2009;Shea et al, 2005).…”
Section: Results Demonstrabilitymentioning
confidence: 99%
“…Many other studies have acknowledged issues of substantial time commitments and workload for online faculty (Bacow et al, 2012;Christianson et al, 2002;Conceição, 2006;DeGagne & Walters, 2010;Green et al, 2009;Haber & Mills, 2008;Mason et al, 2010). Most research has shown that time commitment and workload were barriers or demotivators to faculty, though some studies claimed that the extra time commitment did not affect faculty satisfaction or preference for teaching online (Christianson et al, 2002;Orr et al, 2009;Shea et al, 2005). Some researchers also determined that faculty would not mind the extra time it took to deliver online courses if they were adequately compensated (Haber & Mills, 2008;Huang et al, 2011;Shea, 2007).…”
Section: Results Demonstrabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…These methods leverage the efficacy and scalability of computer and Internet-based technologies and have been used successfully for educational purposes in a number of different settings, particularly in colleges and universities (Sugrue & Rivera, 2005). Research has shown that distance-learning performance outcomes compare favorably to traditional face-to-face instruction (Bernard et al, 2004; Sitzmann, Kraiger, Stewart, & Wisher, 2006; Tallent-Runnels et al, 2006) and in some cases, distance learning can result in better performance and user satisfaction measures when compared to traditional classroom-based courses (Christianson, Tiene, & Luft, 2002; Howard, Schenk, & Discenza, 2003; Kulik, 1986; Lepper & Gurtner, 1989; Roblyer, 1988; Wise & Olson, 1998). …”
mentioning
confidence: 99%
“…One of the most important implications of the study was the recognition of the considerable time needed to plan and deliver an online course. Findings support the viability of courses delivered entirely online (Christianson, Tiene, & Luft, 2002).…”
Section: Review Of the Literaturementioning
confidence: 99%